Ontario’s history of tampering and re-tampering with birth registration documents - Gehl, Lynn (First Peoples Child & Family Review, 2017)
This article opens a discussion on the matter of Ontario administrators’, hospital and government employees’ history of tampering with long form birth registration documents in situations where birth mothers were unmarried or separated. Relying on Indigenous methods, such as listening to personal stories, and experts, the author explores how the practice of tampering with birth documents places Indigenous mothers and children in double jeopardy of not only being denied the information of who their biological father is or was, but also potentially being denied Indian status registration. Mothers and their children are deserving of more. This article ends with arguing additional research and funding are needed for a comprehensive understanding of the issue.